Multilevel meta-analysis of the effect of exercise intervention on inhibitory control in children with ASD - Song, Xiangqin; Hou, Yaoqi; Lei, Zonghan; Zhou, Shenning (Frontiers in Psychology, 2025)
BackgroundInhibitory control deficits represent a core cognitive challenge for children with Autism Spectrum Disorder (ASD), impacting behavioral regulation, social interaction, and adaptive functioning. Exercise interventions have emerged as promising non-pharmacological approaches for cognitive enhancement, yet their specific effects on inhibitory control in the ASD population remain unclear. This study aimed to systematically evaluate the efficacy of exercise interventions on inhibitory control in children and adolescents with ASD.MethodsThis systematic review and multilevel meta-analysis followed PRISMA guidelines and was prospectively registered (PROSPERO: CRD420251039964). We systematically searched five electronic databases (PubMed, Web of Science, Embase, Cochrane Library, and CNKI) from inception to December 2023. Randomized and quasi-randomized controlled trials evaluating exercise interventions for inhibitory control in ASD populations were included. Study quality was assessed using the Cochrane Risk of Bias Tool (ROB2). Effect sizes were calculated as standardized mean differences (SMDs) and synthesized using a three-level meta-analytic approach to account for dependency among effect sizes. Subgroup analyses and meta-regression explored potential moderators of intervention efficacy.ResultsTen studies comprising 466 participants (229 in intervention groups) met inclusion criteria. Exercise interventions demonstrated significant positive effects on inhibitory control in children with ASD (SMD = 0.66, 95% CI [0.44, 0.88]). Structured exercise interventions showed differential efficacy, with Mini Basketball (SMD = 0.95), Martial Arts (SMD = 0.90), and Bicycle Learning (SMD = 0.86) yielding the largest effects. Meta-regression identified total training duration as a significant positive predictor of intervention efficacy (β = 0.027, p = 0.015), while participant age showed a potential negative association (β = −0.091, p = 0.083), suggesting enhanced effectiveness in younger children.ConclusionThis meta-analysis provides robust evidence supporting exercise interventions, particularly structured activities combining physical and cognitive demands, for improving inhibitory control in children with ASD. The findings suggest important clinical implications for intervention design, highlighting the value of adequate intervention duration and early implementation. Future research should address methodological limitations through high-quality trials with standardized protocols and extended follow-up periods.Systamatic reviewCRD420251039964.